2019
DOI: 10.4102/safp.v61i2.5003
|View full text |Cite
|
Sign up to set email alerts
|

The use of emergency hormonal contraception in South Africa: current and future perspectives

Abstract: Emergency hormonal contraceptives play an important role in preventing unplanned pregnancies in South Africa. In this review, we discuss the levonorgestrel emergency contraceptive, the combined estrogen and progestin regimen (also known as the Yuzpe method) and the use of Ulipristal acetate. The levonorgestrel and the combined estrogen, progestin regimen are available in South Africa. The specific mechanisms of action of each of these emergency hormonal contraceptives will be discussed as well as their efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…7 Ordinary combined oral contraceptives can also be used as long as each 12-hourly dose contains at least 100-120 μg EE and a progestin of 0.5-0.6 mg LNG or 1.0-1.2 mg norgestrel. 8 Another option is to use Nordette® as each tablet contains 30 μg EE and 0.15 mg LNG. To attain the acquired dose the woman thus needs to take four Nordette® tablets stat and to repeat the dosage 12 hours later.…”
Section: Yuzpe's Method/regimenmentioning
confidence: 99%
See 4 more Smart Citations
“…7 Ordinary combined oral contraceptives can also be used as long as each 12-hourly dose contains at least 100-120 μg EE and a progestin of 0.5-0.6 mg LNG or 1.0-1.2 mg norgestrel. 8 Another option is to use Nordette® as each tablet contains 30 μg EE and 0.15 mg LNG. To attain the acquired dose the woman thus needs to take four Nordette® tablets stat and to repeat the dosage 12 hours later.…”
Section: Yuzpe's Method/regimenmentioning
confidence: 99%
“…9 Other studies have reported an efficacy of 98-99% in preventing pregnancies. 8 The sooner after unprotected coitus it is used, the more effective it is. This is also generally true for all methods of EC.…”
Section: Yuzpe's Method/regimenmentioning
confidence: 99%
See 3 more Smart Citations